Experimental investigation on the seismic performance of PP-band strengthening stone masonry houses - Sathiparan, N.; Sakurai, K.; Numada, M.; Meguro, K. (Springer, 2013)
The collapse of stone masonry is one of the greatest causes of death in major earthquake events around the world. This paper investigates a recently developed retrofitting technology specifically aimed at preventing or prolonging the collapse of stone masonry buildings under strong earthquakes. This technology uses common polypropylene packaging straps to form amesh, which is then used to prevent or prolong collapse. This paper examines the findings from static and dynamic testing of the proposed retrofit. It is shown that the proposed technique effectively prevents brittle masonry collapse and the loss of debris
Keywords: Stone masonry; PP-band retrofitting